The Relation Between Serum-based Systemic Inflammatory Biomarkers and Locoregional Lymph Node Metastasis in Clinical Stages I to II Right-sided Colon Cancers: The Role of Platelet-to-Lymphocyte Ratio - Lale, Azmi; Sahin, Ertugrul; Aslan, Ahmet; Can, Omer Faruk; Ebiloglu, Mehmet Fatih; Aygen, Erhan (Lippincott Williams & Wilkins, 2023)
Background:It aimed to evaluate the relationship between the systemic inflammatory markers and the lymph node metastasis in clinical stages I to II right-sided colon cancers.Patients and Methods:A total of 51 eligible clinical stages I to II right-side located colon cancer patients were included in the study. Complete mesocolic excision and central vascular ligation procedures were performed in all cases. All the patients were divided into 2 main groups, pN- (n = 22) and pN+ (n = 29). Demographic parameters, preoperative serum-based inflammatory biomarkers, and histopathological findings were compared between the groups.Results:The mean age was 61.0 (54 to 71) years. Of the patients, 51.0% (26/51) were females. The open surgical approach was performed on 54.9% (28/51) of the patients and 45.1% (23/51) was performed laparoscopy. The mean total number of retrieved lymph nodes was 29.1. The lympho-vascular invasion was significantly higher in the pN+ group (89.7% vs 50.0%). There were no significant differences in neutrophil-to-lymphocyte ratio, C-reactive protein-to-albumin ratio, mean platelet volume-to-platelet ratio, hemoglobine-albuminelymphocyte-platelet score, systemic inflammation index, lymphocyte-to-monocyte ratio, neutrophil-to-monocyte ratio, lymphocyte-to-C-reactive protein ratio (LCR), neutrophil-to-albumin ratio, and prognostic nutritional index. However, the mean platelet-to-lymphocyte ratio (PLR) was significantly lower in the pN+ group (pN-: 282.1 vs pN+: 218.7, P = 0.048). The cutoff value for PLR was determined as 220 according to receiver operating characteristic analysis, with a 63.6% sensitivity and 65.6% specificity.Conclusion:Although it has limited sensitivity and specificity, decreased preoperative PLR was significantly associated with lymph node metastasis in patients with clinical stages I to II right-sided colon cancer. It should be considered as a biomarker for nodal involvement when planning treatment strategies.
Keywords: colon cancer; inflammatory biomarkers; lymph node metastasis; lymphocyte; neutrophil; platelet